B Sc graduate output - a success indicator of access programs at Walter Sisulu University - Mathews, Mary (South African Journal of Higher Education, 2016)
This research set out to evaluate whether the periodic review, adaptations and implementation strategies in the B Sc access programs with foundation provision in the Faculty of Science Engineering and Technology at Walter Sisulu University from 1998 to 2007 have had any impact on the number of B Sc graduates produced. The study also evaluated whether the programs addressed issues such as redress, access and success for which they were initiated in conjunction with government policies and available resources. A longitudinal action research that involved review of program models, selection criteria, curriculum, pedagogy, assessment, monitoring and impact was carried out. Data was collected annually from 1998 to 2011 and a three phase analysis was made. The overall analysis indicated that the programs afford an alternate entry point to higher education and training (HET) to aspiring science matriculates in a semi urban/rural catchment area providing redress and access. The students from the programs from 1998 to 2007 (without considering the effects of attrition and migration) have made a commendable 14% contribution to the annual FSET number of B Sc graduates where the annual allowed intake of access students is about 15%. Key words: Access, foundation provision, extended programs, academic development, success, graduation